Randomized Controlled Trials on Intracerebral Hemorrhage: A Cross Sectional Retrospective Analysis of CONSORT Item Adherence - Jauch, Kirstin; Kowark, Ana; Coburn, Mark; Clusmann, Hans; Höllig, Anke (Frontiers in Neurology, 2019)
Object: Intracranial hemorrhage (ICH) is the second most common cause of stroke but still there is little consolidated knowledge about the optimal treatment strategies (e.g. the benefit of surgical evacuation). We evaluated the current randomized controlled trials (RCTs) on primary ICH (01.2013 – 03.2017) according to their fulfillment of the CONSORT statement´s criteria (published in 2010) –as a marker of transparency and quality of study planning and realization. Methods: A Pubmed search using the search terms ((cerebral hemorrhage) OR (hemorrhagic stroke) OR (intracerebral hemorrhage) OR ich OR (intracranial hemorrhage) OR (intracranial bleeding) OR (intracerebral hematoma) OR (intracranial hematoma)) AND ((randomized controlled) OR randomised OR RCT) was carried out (01.2014 – 3.2017, respectively 01.2013 – 12.2013). Abstracts were screened for inclusion. Eligible full text manuscripts were assessed for the implementation of the CONSORT criteria. Citation frequencies and impact factors of the journals were related to ratio of CONSORT criteria fulfillment. Results: Overall 1128 abstracts were screened for inclusion; 31 studies were suitable for final analysis. A mean fulfillment ratio of 54% (± 22%) was found. A high correlation between impact factor and adherence to CONSORT criteria was shown (r=0.7586; p<0.0001). Citation frequency per year was related to ratio of CONSORT item fulfillment (r=0.6552; p<0.0001) and to the impact factor of the publishing journal (r=0.7478; p<0.0001). Of note, the items 10 (randomization: implementation) and 21 (generalizability) showed particularly high rates of non-fulfillment (both 84%). The majority of studies (97%) complied with item 2b (specific objectives or hypotheses), but strikingly objectives were mostly described vaguely. Other essential criteria such as sample size determination, definition of outcome parameters and participant flow were only fulfilled weakly (55, 61 and 45%). Conclusions: Over 20 years after its inception there is still weak adherence to the CONSORT statement. As a consequence, conclusions are hampered by inadequate planning and/or reporting. Particularly with respect to pathologies as ICH lacking clear, evidence-based guidelines adherence to the CONSORT statement might improve research quality in order to define valuable treatment strategies.